1764 Meet Kaya : An American Girl - Book 1 - Shaw, Janet Beeler, 1937-; Farnsworth, Bill; McAliley, Susan (Middleton, WI : Pleasant Company, 2002)
In 1764, when Kaya and her family reunite with other Nez PercGe Indians to fish for the red salmon, she learns that bragging, even about her swift horse, can lead to trouble. Includes historical notes on the Nez PercGe Indians.
At head of title: 1764.
Keywords: Pride and vanity -- Fiction; Conduct of life -- Fiction; Horses -- Fiction; Nez PercGe Indians -- Fiction; Indians of North America -- Fiction -- Northwest, Pacific; Northwest, Pacific -- Fiction